PERENCANAAN DAN PERANCANGAN STASIUN KERETA API PADA BANDAR UDARA AHMAD YANI DI KOTA SEMARANG - Rian Mas Nugroho; Agus Heru Purnomo; Edi Pramono Singgih (Universitas Sebelas Maret Surakarta, 2017)
The railway station at Ahmad Yani airport in Semarang is a work of architecture discipline. The goal is to get the design of the airport train station in Semarang. With the railway station at Ahmad Yani Airport Semarang is to facilitate passengers who want to continue their journey, either from plane to train or vice versa. It is also expected that with this railway station can reduce congestion that occurred in Semarang, people outside Semarang who want to pick up his family at the airport do not have to come all the way to Ahmad Yani airport, because passengers domiciled outside the Semarang can Use a train to get to their respective areas. By using the accessibility method, it is expected that this station can facilitate the passengers who want to use rail transportation modes or who want to change the mode of transportation. Of course, the selection of the site has also been through several analyzes. The chosen site is also very precise because it is on the south side of the Ahmad Yani airport and is on the railway line. And also on the east side of the tread is the main road to get to the airport. So, on the highway is access to the station. The shape, layout and location of the station building also prioritizes the accessibility of its users. The facilities provided are also designed to facilitate passengers such as the addition of escalators, travellators, ramps, guiding blocks, bridges, etc. The concept used indirectly can provide convenience and comfortable of the passengers who want to change the mode of transportation. Keywords: railway station, airport station, intermodal transportation integration, accessibility